EPIDEMIOLOGY OF IMPORTED MALARIA IN THE MEDITERRANEAN REGION - Silvia Odolini; Philippe Gautret; Philippe Parola (Mediterranean Journal of Hematology and Infectious Diseases)
Malaria is one of the most widespread infectious diseases of our time, causing approximately one million deaths, most of them in sub-Saharan Africa and under the age of 5. During the last few years the number of imported malaria cases in Europe has decreased, but several imported malaria cases are still reported in Europe and Mediterranean countries, probably supported by the increasing number of international travel in association with the enormous influx of immigrants from malaria-endemic countries. Moreover, the presence of Anopheline vectors in Mediterranean countries, the returned infected travellers as a source of parasite and climate changes may result in the reappearance of malaria in countries where it was previously eradicated, such as Greece in the recent years. Several cases of autochthonous malaria have recently been reported to support the need of an ongoing surveillance for mosquito control and an increased vigilance by health professionals. Aim of this review is to explore all literature about imported malaria in Mediterranean areas and the potential consequences of this, providing a critical comprehensive revision of actual knowledge.